Pengaruh Mekanisme Good Corcoporate Governance (GCG), Kinerja Lingkungan, dan Pengungkapan Corporate Social Responsilibility (CSR) Terhadap Kinerja Keuangan Perusahaan - Maudina Rachamawati; Andry Arifian Rachman (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The decline in financial performance of a number of companies has highlighted the importance of examining governance and social responsibility factors that could potentially impact financial performance. This study aims to analyze the influence of Good Corporate Governance (GCG) mechanisms, environmental performance, and Corporate Social Responsibility (CSR) disclosure on corporate financial performance. The study was conducted on companies listed on the Indonesia Stock Exchange (IDX) in the Basic Chemical, IT & Service Consulting, Personal Care Products, Real Estate Development & Management, and Software subsectors from 2022 to 2024. This study employed a quantitative approach with secondary data obtained from the companies' annual reports and financial statements. The analysis technique used was multiple linear regression to examine the influence of the number of board members, board members, audit committee members, environmental performance, and CSR disclosure on financial performance. The results showed that GCG mechanisms, proxied by the number of board members and board members, had no significant effect on financial performance, while the audit committee had a positive effect. Environmental performance and CSR disclosure did not significantly influence financial performance.